Corrigendum: Between-Subject and Within-Subject Variation of Muscle Atrophy and Bone Loss in Response to Experimental Bed Rest - Böcker, Jonas; Schmitz, Marie-Therese; Mittag, Uwe; Jordan, Jens; Rittweger, Jörn (Frontiers in physiology, 2022)
[This corrects the article DOI: 10.3389/fphys.2021.743876.].